2018
DOI: 10.14301/llcs.v9i3.491
|View full text |Cite
|
Sign up to set email alerts
|

MatCH (Mothers and their Children’s Health) Profile: offspring of the 1973-78 cohort of the Australian Longitudinal Study on Women’s Health

Abstract: MatCH (Mothers and their Children's Health) is a nationwide Australian study to investigate the links between the history of health, wellbeing and living conditions of mothers and the health and development of their children. MatCH builds on the Australian Longitudinal Study on Women's Health (ALSWH), which began in 1996 and has surveyed more than 58,000 women in four nationally representative age cohorts. MatCH focuses on the three youngest offspring of the cohort of ALSWH participants randomly sampled from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Non‐adherence to recommendations for maximum screen time varies with age, and the possibility of under‐reporting — the MatCH sample consisted of women with some characteristics associated with better adherence to guidelines (higher levels of education and work force participation) — means that it may be greater than we have estimated. The rapid uptake of screens by children before their third birthday is of particular concern because greater screen time increases the risk of poorer developmental outcomes .…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Non‐adherence to recommendations for maximum screen time varies with age, and the possibility of under‐reporting — the MatCH sample consisted of women with some characteristics associated with better adherence to guidelines (higher levels of education and work force participation) — means that it may be greater than we have estimated. The rapid uptake of screens by children before their third birthday is of particular concern because greater screen time increases the risk of poorer developmental outcomes .…”
mentioning
confidence: 87%
“…We analysed data collected in 2015 for 3063 mothers in the 1973–1978 birth cohort of the Australian Longitudinal Study on Women's Health (age, 37–42 years), and data collected in 2016–17 for their 5780 children in the Mothers and their Children's Health (MatCH) study . Human research ethics committees at the Universities of Newcastle (references, H‐076‐0795, H‐2014‐0246) and Queensland (references, 2004000224, 2014001213) approved both studies; all mothers provided informed consent.…”
mentioning
confidence: 99%
“…Sub-sample 2 were 708 children (and their mothers) who were eligible for having data from the Australian Early Development Census (AEDC). 26 Full details of the eligibility and exclusion criteria for both these sub-samples are shown in Supplementary Fig. S1a and 1b, while characteristics of the mothers included in the ASQ and AEDC analyses versus those not included are presented in Supplementary Tables S2a and 2b. The Human Research Ethics Committees at the University of Newcastle and the University of Queensland approved both studies.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…22 In 2016, invitations to be part of the Mothers and their Children's Health (MatCH) sub-study were sent to ALSWH participants who (1) had not died or withdrawn, (2) had consented to be contacted about sub-studies, and (3) had not reported infertility. 23 For the current study, mothers also had to have completed an ALSWH survey while pregnant with a MatCH child. Mothers were asked to report on their three youngest children aged under 13 years (ie born from 2004 onwards), and the response to MatCH for women known to be mothers was 48%.…”
Section: Participant Selectionmentioning
confidence: 99%
“…Compared to the overall 1973-1978 ALSWH cohort, mothers who participated in MatCH were more likely to have a university education, be employed, and not smoke. 23 ALSWH data were collected at approximately 3-yearly intervals between 1996…”
Section: Participant Selectionmentioning
confidence: 99%